Role of Pharmacogenetic Testing in the Risk and Safety Assessment of Valproates: The Ethnic Aspect (Review) - N. A. Shnayder; V. V. Grechkina; V. V. Arkhipov; R. F. Nasyrova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
INTRODUCTION. Pharmacogenetic (PGx) testing plays a significant role in predicting the risk of adverse drug reactions (ADRs) associated with valproic acid (VPA) products, which are among the most prescribed medicinal products in neurology and psychiatry. However, the sensitivity and specificity of PGx screening panels may be insufficient as individual valproate metabolism varies across ethnically/racially diverse patient populations.AIM. The study aimed to identify implementation areas for a personalised approach to the development of PGx panels for assessing the safety and risk of valproate therapy in various ethnic and racial groups residing in the Russian Federation.DISCUSSION. The authors reviewed the results of population studies concerning the frequency of non-functional and low-function alleles of genes encoding isoenzymes that play key roles in VPA P-oxidation in the liver. This review focused on studies published in eLIBRARY.RU, PubMed, Scopus, and Google Scholar in 2012-2022. The inclusion criteria were full-text original articles, systematic reviews, meta-analyses, Cochrane reviews, and clinical cases in Russian or English. The analysis revealed that the need for personalised assessment of the risk and safety of VPA may depend on the frequency of risk alleles for slowing down VPA P-oxidation in the liver across racial and ethnic groups worldwide, and particularly in Russia. The authors identified new areas to implement the personalised approach to the development of PGx panels for assessing the safety and risk of valproate therapy with consideration of the rates of hepatic VPA P-oxidation in patients of different ethnic and racial backgrounds. However, the review of population-based associative genetic research from around the world demonstrated the current lack of clarity in the prospects of translating international findings directly into Russian clinical practice through the development of PGx panels due to Russia's ethnic/racial diversity and vast territory.CONCLUSIONS. To increase the sensitivity and specificity of Russian PGx panels, bridging studies are required to extrapolate the associations established between the most common risk alleles and VPA P-oxidation disorders in other ethnic groups to a specific population of a specific Russian region.